Dr. Andres Gantous — Deep Plane Facelift — Vaughan - Gantous, Andres (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Andres Gantous, practicing in Vaughan, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003271; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; vaughan